Semiotic Analysis of Jokowi’s Instagram Account About G20 - Faisal Mohamed Kadir; Daniel Susilo (Jurnal Audience: Jurnal Ilmu Komunikasi, 2023)
Indonesia has the honor to be the leader of G20 forum. As the country with unique diversities, its great economy and social development, also leadership dynamics have led to urgency to analyze Indonesian performance in G20, that includes the president of Indonesia named Jokowi. Jokowi has been a great spotlight for Indonesia in almost a decade; therefore, the data is more than enough to be analyzed with semiotic analysis. Saussure’s semiotic analysis has its in-depth technique regarding the language dynamics since Indonesia is strongly affiliated to social alignment. Jokowi’s performance is placed in his Instagram account, using Saussure’s Semiotic analysis we could discover strong multivectorism results in his identity politics in his diplomatic interest behind Jokowi and G20 forum. To understand and discover is to prepare and improve for the better research perspective around the government.Keywords: Multivectorism; Identity Politics; Jokowi; G20 Forum; Diplomatic Interest